2000
DOI: 10.1046/j.1365-2230.2000.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary cutaneous metastasis on the buttock: a disclosing sign of pancreatic adenocarcinoma

Abstract: A 48-year-old man, previously healthy and asymptomatic, showed a unique skin lesion located on the right buttock. The histopathological study of the lesion disclosed an adenocarcinoma metastatic to the skin. The primary tumour was found at the head of the pancreas, and was confirmed by biopsy. Six months after the beginning of treatment with Gemcitabine the patient is still asymptomatic, and the cutaneous lesion has disappeared. Carcinomas of the pancreas represent less than 5% of human malignant neoplasms, sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…To our knowledge, this is the second reported case of pancreatic cancer with cutaneous metastasis in the English and Japanese published work that has been treated with gemcitabine. In both the previously reported case and our case, the metastatic skin lesions have responded remarkably to gemcitabine treatment 9 . Furthermore, the drug‐related toxicity was mild in both patients; the case reported by Floerez et al .…”
supporting
confidence: 79%
“…To our knowledge, this is the second reported case of pancreatic cancer with cutaneous metastasis in the English and Japanese published work that has been treated with gemcitabine. In both the previously reported case and our case, the metastatic skin lesions have responded remarkably to gemcitabine treatment 9 . Furthermore, the drug‐related toxicity was mild in both patients; the case reported by Floerez et al .…”
supporting
confidence: 79%
“…Takeuchi et al13) revealed that the tail of the pancreas was the most common site of the primary tumor, and the gross appearance of the cutaneous tumors in that study was oval, firm, solid, non-painful nodules. Although an excellent response to gemcitabine has been reported on in one case report14), most of the patients died within 7 months.…”
Section: Discussionmentioning
confidence: 88%
“…They represent less than 1% of all gastrointestinal malignancies that are able to develop skin metastases. However, other described sites of skin spread include back, forearms, 156 buttock, 157 axilla, and chest. 154,155 Clinically, these lesions appear as cutaneous or subcutaneous nodules and infiltrated plaques in the abdominal wall.…”
Section: Pancreatic Carcinomamentioning
confidence: 99%